2012
DOI: 10.1074/jbc.m112.368613
|View full text |Cite
|
Sign up to set email alerts
|

Monoubiquitination Promotes Calpain Cleavage of the Protein Phosphatase 2A (PP2A) Regulatory Subunit α4, Altering PP2A Stability and Microtubule-associated Protein Phosphorylation

Abstract: Background: ␣4 binds to the PP2A catalytic subunit and the microtubule-associated E3 ligase MID1. Results: MID1-dependent monoubiquitination promotes calpain-mediated cleavage of ␣4, altering its phosphatase regulatory function. Conclusion: Defects in this regulatory process may underlie the MAP hypophosphorylation and hyperphosphorylation seen in Opitz syndrome and Alzheimer disease. Significance: Pharmacological agents that interfere with ␣4 monoubiquitination or cleavage are potential therapeutics to treat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 39 publications
1
41
1
Order By: Relevance
“…Our results showing polyubiquitination of ␣4 are in contrast to a recent report by Watkins et al (25), which showed only monoubiquitination of full-length ␣4 by MID1 when using UbcH5b (UBE2D2) and UbcH5c (UBE2D3) as the E2 enzymes (25). It was reported that monoubiquitination of ␣4 promotes its cleavage by calpain, and that this results in increased processing of PP2Ac (25).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Our results showing polyubiquitination of ␣4 are in contrast to a recent report by Watkins et al (25), which showed only monoubiquitination of full-length ␣4 by MID1 when using UbcH5b (UBE2D2) and UbcH5c (UBE2D3) as the E2 enzymes (25). It was reported that monoubiquitination of ␣4 promotes its cleavage by calpain, and that this results in increased processing of PP2Ac (25).…”
Section: Discussioncontrasting
confidence: 56%
“…An increase in PP2Ac levels and decreased serine/threonine phosphorylation of cytoskeletal proteins seen in patient fibroblasts supports the notion that proper regulation of the microtubule associated PP2A activity is critical for normal development (9,10). Recent data suggest that ␣4 can play both a protective and destructive role in regulating PP2A activity and that this functionality is dependent on its monoubiquitination by MID1 (25). Given the promiscuity of PP2A, the MID1-␣4-PP2Ac complex likely participates in the regulation of many different cellular processes.…”
Section: Alpha4 (␣4) Is a Key Regulator Of Protein Phosphatase 2a (Ppmentioning
confidence: 50%
See 1 more Smart Citation
“…However, MID1‐catalyzed monoubiquitylation of α4 at unidentified lysine residues induces its cleavage at Phe 255 –Gly 256 by calpain, negating its effect on PP2c stabilization (Watkins et al . 2012). Interestingly, MID1 was also shown to polyubiquitylate PP2c and thereby to mark it for degradation (Trockenbacher et al .…”
Section: Regulation Of Neuronal Proteins By Monoubiquitylationmentioning
confidence: 99%
“…We have shown previously that in allergic airways disease models (AAD) and in patients with asthma, TRAIL is released by structural airway cells in response to allergen stimulation [28] resulting in upregulation of the E3 ubiquitin ligase Midline-1 (MID1) [29]. MID1 in turn monoubiquinates the α4 subunit of protein phosphatase 2A (PP2A), promoting the proteosomal degradation of the catalytic subunit of PP2A (PP2ac) and preventing the A and B subunits forming an active complex [30, 31]. Due to the central role of PP2A in the regulation of inflammatory cascades via dephosphorylation, including the NF-κB and MAP kinase pathways [32, 33], the inhibition of PP2Ac permits the activation of inflammatory cascades, primarily through T H 2 mediated mechanisms but also through early inflammatory factors such as CCL11, CCL20, IL-25 and 33 [28, 29, 34].…”
Section: Introductionmentioning
confidence: 99%